Controlled Growth of Indium Selenides by High-Pressure and High-Temperature Method - Dai, Yajie; Zhao, Shouxin; Han, Hui; Yan, Yafei; Liu, Wenhui; Zhu, Hua; Li, Liang; Tang, Xi; Li, Yang; Li, Hui; Zhang, Changjin (Frontiers in Materials, 2022)
The controlled growth of indium selenides has attracted considerable research interests in condensed matter physics and materials science yet remains a challenge due to the complexity of the indium–selenium phase diagram. Here, we demonstrate the successful growth of indium selenides in a controllable manner using the high-pressure and high-temperature growth technique. The γ-InSe and α-In2Se3 crystals with completely different stoichiometries and stacking manner of atomic layers have been controlled grown by subtle tuning growth temperature, duration time, and growth pressure. The as-grown γ-InSe crystal features a semiconducting property with a prominent photoluminescence peak of ∼1.23 eV, while the α-In2Se3 crystal is ferroelectric. Our findings could lead to a surge of interest in the development of the controlled growth of high-quality van der Waal crystals using the high-pressure and high-temperature growth technique and will open perspectives for further investigation of fascinating properties and potential practical application of van der Waal crystals.